2012
DOI: 10.1007/s10853-012-6517-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose-based membrane-like biodegradable composites using cross-linked and noncross-linked polyvinyl alcohol

Abstract: Bacterial cellulose (BC)-based membrane-like biodegradable composites were produced by immersing wet BC pellicles in polyvinyl alcohol (PVA) solution. The BC content in the BC-PVA composites can be adjusted by varying the concentration of PVA solution. Chemical cross-linking of PVA was carried out using glutaraldehyde to increase the mechanical properties of the composites as well as to make the PVA partially to highly water insoluble. Examination by scanning electron microscopy indicated that the PVA not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…29 For the CBC membrane, the first, second and third weight loss occurred at 40-120℃, 240-350℃ and 350-600 ℃, respectively. The TGA curve of BC having three weight loss steps can be assigned to: the first weight loss (40-130℃) due to water loss, the second weight loss (300-360℃) owing to the main chain decomposition and the third weight loss (360-600 ℃ ) attributed to the residual main chain decomposition.…”
Section: Tgamentioning
confidence: 94%
See 1 more Smart Citation
“…29 For the CBC membrane, the first, second and third weight loss occurred at 40-120℃, 240-350℃ and 350-600 ℃, respectively. The TGA curve of BC having three weight loss steps can be assigned to: the first weight loss (40-130℃) due to water loss, the second weight loss (300-360℃) owing to the main chain decomposition and the third weight loss (360-600 ℃ ) attributed to the residual main chain decomposition.…”
Section: Tgamentioning
confidence: 94%
“…3b, and their mechanical properties are compared in Table 1. 29 For the CBC case, the diffraction peaks displayed at 2θ = 14.58°, 17.08° and 22.71°. In the case of CBC-IL membrane, however, the value of tensile strength increased up to 44.26 MPa and it means increase by 12.4% compared with the pure CBC; in particular, the soft CBC-IL composite membrane exhibits an exceptionally superior elongation, up to 22%, which is better than that of BC and CBC membranes.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…It is clear that the MFC fibers are capable of homogenously filling the pores present in the BC nanofiber network structure and, thus, eliminating many potential weak points (pores or voids) in the BC network. Earlier researchers have shown that the BC pellicles have large amounts of pores or voids that are somewhat uniformly distributed [5]. Such structures have made BC membranes suitable for ultrafiltration [1].…”
Section: Tensile Properties Of Bc-mfc Hybrid and Bc-mfc-spi Nanocompomentioning
confidence: 99%
“…However, BC fibers have diameters that range between 55 and 60 nanometers and display many unique characteristics, such as high purity and high water-holding capacity [1,2]. Due to their high crystallinity, high degree of polymerization, and higher molecular orientation they also have high strength and stiffness (Young s modulus), as well as higher thermal stability compared to conventional plant-derived cellulose fibers [1,[3][4][5]. BC membranes obtained through static fermentation tend to have a highly porous structure combined with strong biocompatibility [1,[6][7][8][9] and excellent environmental biodegradability [3][4][5]10] and, importantly, their size, shape, and thickness can be easily controlled [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation